Reward‐related brain structures are smaller in patients with schizophrenia and comorbid metabolic syndrome. (27th September 2018) - de Nijs, J.; Schnack, H. G.; Koevoets, M. G. J. C.; Kubota, M.; Kahn, R. S.; van Haren, N. E. M.; Cahn, W.
Abstract : Objective: Metabolic syndrome (MS) is highly prevalent in schizophrenia and often a consequence of unhealthy behaviour. Reward‐related brain areas might be associated with MS, since they play a major role in regulating health behaviour. This study examined the relationship between MS and brain volumes related to the reward system in schizophrenia. Method: We included patients with schizophrenia, with MS (MS+; n = 23), patients with schizophrenia, without MS (MS−; n = 48), and healthy controls ( n = 54). Global brain volumes and volumes of (sub)cortical areas, part of the reward circuit, were compared between patients and controls. In case of a significant brain volume difference between patients and controls, the impact of MS in schizophrenia was examined. Results: Patients had smaller total brain (TB; P = 0.001), GM ( P = 0.010), larger ventricles ( P = 0.026), and smaller reward circuit volume ( P < 0.001) than controls. MS+ had smaller TB ( P = 0.017), GM ( P = 0.008), larger ventricles ( P = 0.015), and smaller reward circuit volume ( P = 0.002) than MS−. MS+ had smaller orbitofrontal cortex (OFC; P = 0.002) and insula volumes ( P = 0.005) and smaller OFC ( P = 0.008) and insula cortical surface area ( P = 0.025) compared to MS−. Conclusion: In schizophrenia, structural brain volume reductions in areas of the reward circuitry appear to be related to comorbid MS.